The impact of the overhead line's power supply system spatial differentiation on the energy consumption of trolleybus transport: planning and economic aspects - Bartłomiejczyk, Mikołaj; Połom, Marcin (Transport, 2017)
Nowadays the issue of electric energy saving in public transport is becoming a key area of interest, which is connected both with a growth in environmental awareness of the society and an increase in the prices of fuel and electricity. It can be achieved by reducing of the transmission losses in supply system or by the improving of the usage of the regenerative breaking. The spatial differentiation of the energy supply system of public transport is one of the elements, which has significant impact on the energy consumption. Paper presents the theoretical analysis of the impact of supply system topology on the energy consumption and extensive measurement analysis realized in Gdynia (Poland) trolleybus system.First published online: 13 Oct 2015